2021
DOI: 10.1038/s41396-021-00937-7
|View full text |Cite
|
Sign up to set email alerts
|

Key bacterial taxa and metabolic pathways affecting gut short-chain fatty acid profiles in early life

Abstract: Infant gut microbiota development affects the host physiology throughout life, and short-chain fatty acids (SCFAs) are promising key metabolites mediating microbiota-host relationships. Here, we investigated dense longitudinally collected faecal samples from 12 subjects during the first 2 years (n = 1048) to identify early life gut SCFA patterns and their relationships with the microbiota. Our results revealed three distinct phases of progression in the SCFA profiles: early phase characterised by low acetate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
135
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(172 citation statements)
references
References 70 publications
17
135
0
Order By: Relevance
“…This observation indicates that an age-appropriate gut microbiome development may be important for protection against respiratory infection. In a recent study, Tsukuda et al reported SCFA and other organic acid profiles in stool samples during the first 2 years of age from a small cohort of mainly breastfed and vaginally born infants [ 51 ]. An early succinate peak was paralleled by increasing acetate, while propionate and butyrate increased with cessation of breastfeeding.…”
Section: Discussionmentioning
confidence: 99%
“…This observation indicates that an age-appropriate gut microbiome development may be important for protection against respiratory infection. In a recent study, Tsukuda et al reported SCFA and other organic acid profiles in stool samples during the first 2 years of age from a small cohort of mainly breastfed and vaginally born infants [ 51 ]. An early succinate peak was paralleled by increasing acetate, while propionate and butyrate increased with cessation of breastfeeding.…”
Section: Discussionmentioning
confidence: 99%
“…We cannot fully represent the complexities of the infant gut microbiota, and any generated hypotheses must necessarily be validated in in vitro and in vivo conditions. Detailed analysis of the infant microbiota has revealed a species composition that is much more diverse in both species and metabolites than our model results show [4, 64]. There is future work to be done to further study the relevant factors in the infant gut, and to bring these results into a more realistic model context.…”
Section: Discussionmentioning
confidence: 83%
“…Acetate and lactate are produced by Bifidobacterium spp in the characteristic bifid shunt, which produces acetate and lactate in a 3:2 ratio [15]. Formate, hydrogen, ethanol and succinate are also all reported in infant feces [9, 25, 59, 64].…”
Section: Resultsmentioning
confidence: 99%
“…Notably, we associated higher abundances of members of the Lachnospiraceae family, including butyrate-producing taxa, with higher anti-meningococcal antibody responses. The abundance of these bacteria in the gut typically increases following the cessation of breastfeeding 41,44 , and are generally found to be beneficial for the developing immune system 45 .…”
Section: Discussionmentioning
confidence: 99%